Critical contributions for a look at health and safety at work - Carreño Hernández, Ismael E.; Riaño Peña, Camilo A. (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The goal of this article is to highlight the importance of what the development in the area of security and health at work as an indispensable element for human dignity. This analysis made from a critical thought with contributions coming from different discipline to the law in search of interdisciplinary support to the defense of its formulation and carrying it out as a fundamental right. Based on the compilation of the process of forming societies in particular the Colombian one, around work and labor occupation, it has shown the influence that the explosion of the cost associated with the problems of the performance of workers in their functions, in terms of productivity, which have been a deciding factor in the labour unions processes; to conclude the birth of jobs in favor of workers are exposed, this is where the analizad category arises. To finalize some general observations are presented that pretend to center the analysis made in some specific aspects.